Labour taxes and international trade: The role of domestic labour value added - Amat Adarov; Mario Holzner; Branimir Jovanović; Goran Vukšić (The Vienna Institute for International Economic Studies (wiiw), 2021)
This paper revisits the relationship between labour taxation and international trade, focusing on the role of domestic labour value added. Using sectoral data from 41 EU and OECD economies over the period 2005- 2014, we assess how labour taxes affect exports and imports and how domestic labour value added shapes this relationship. We find that higher labour taxes reduce exports but that the effect depends to a large extent on the share of domestic labour value added, which differs by industries, countries and time periods. Imports do not seem to be affected. This implies that changes in labour taxes will not affect all sectors and countries in the same way and that policy makers should be aware of this when deciding on labour taxes. We also calculate the contribution of labour tax changes to the export dynamics in the analysed period and sample of countries, finding that in general the contribution is small.
Keywords: F14; F16; H24; J32; 330; taxation; labour; international trade; exports; imports; labour share